PENGARUH PELATIHAN DAN LINGKUNGAN ORGANISASI TERHADAP KOMPETENSI SERTA DAMPAKNYA TERHADAP KINERJA PENYULUH PERTANIAN (Studi Pada Dinas Pertanian Dan Peternakan Daerah Provinsi Sulawesi Utara) - Moch. Toha Khuseno (AGRI-SOSIOEKONOMI, 2019)
This study aims to determine the effect of training on Agricultural Extension competencies; know the effect of the organization's environment on Agricultural Extension competencies; know the effect of training on the performance of Agricultural Extension Workers; know the effect of the organizational environment on the performance of Agricultural Extension Workers; know the training factors and organizational environment on the performance of Agricultural Extension Workers through work competence as an intervening variable. This research was carried out using the exploratory method with a quantitative approach with the research location at the North Sulawesi Provincial Agriculture and Animal Husbandry Department. The number of samples is equal to the total population of 18 people given the small population. Data collection methods used are descriptive statistical analysis and inferential statistical analysis using path analysis with t-test as hypothesis testing. The results showed that training for Agricultural Extension Workers had a significant effect on work competence; the organizational environment also significantly influences the work competency of Agricultural Extension Workers; work Competence has a significant effect on the performance of Agricultural Extension Workers; Training also has a significant effect on the performance of Agricultural Extension Workers; the organizational environment has a positive and significant effect on the performance of agricultural instructors; training and Organizational Environment have a significant effect on the performance of Agricultural Extension Workers through their Work Competencies. There is an increase in the direct influence and indirect effect of each variable. *eprm*